Cost-Utility Analysis of 1- and 2-Level Dorsal Lumbar Fusions With and Without Recombinant Human Bone Morphogenic Protein-2 at 1-Year Follow-Up. Issue 1 (February 2016) - Alvin, Matthew D.; Derakhshan, Adeeb; Lubelski, Daniel; Abdullah, Kalil G.; Whitmore, Robert G.; Benzel, Edward C.; Mroz, Thomas E.
Abstract : Study Design: A retrospective 1-year cost-utility analysis. Objective: To determine the cost-effectiveness of using recombinant human bone morphogenic protein (rhBMP-2) in addition to autograft for 1- and 2-level lumbar fusions. Summary of Background Data: rhBMP-2 has been studied extensively to identify its benefits, risks, patient outcomes, and costs relative to autograft [local bone or iliac crest bone graft (ICBG)]. This study seeks to analyze the cost-effectiveness of adding rhBMP-2 to autograft versus without rhBMP-2 in lumbar fusions. Methods: Thirty-three patients receiving rhBMP-2 in addition to either local bone autograft or ICBG (rhBMP-2 cohort) and 42 patients receiving only local bone autograft or ICBG (control cohort) for 1- or 2-level dorsal lumbar fusion were analyzed. This included posterolateral fusion, posterior lumbar interbody fusion, and transforaminal lumbar interbody fusion. One-year postoperative health outcomes were assessed based on Visual Analogue Scale, Pain Disability Questionnaire, Patient Health Questionnaire, and EuroQol-5 Dimensions questionnaires. Direct medical costs were estimated using Medicare national payment amounts and indirect costs were based on patient missed work days and patient income. Postoperative 1-year cost-utility ratios and the incremental cost-effectiveness ratio (ICER) were calculated to assess for cost-effectiveness using a threshold of 100, 000/QALY gained. Results: The 1-year cost-utility ratio (total cost/ΔQALY) for the control cohort was significantly lower (143, 251/QALY gained) than that of the rhBMP-2 cohort (272, 414/QALY gained) ( P <0.01). At 1-year follow-up, the control group dominated the ICER compared with the rhBMP-2 group. Conclusions: Statistically significant and clinically relevant improvements (through minimum clinically important differences) were seen for both cohorts. In the ICER analysis, the control cohort dominated the rhBMP-2 group. Assuming durable per year gains in QALY, by 2 years fusion with autograft but without rhBMP-2 would be considered cost-effective (71, 625/QALY gained), whereas fusion with both autograft and rhBMP-2 would not be cost-effective (136, 207/QALY gained).